Honey: A Therapeutic Agent for Disorders of the Skin - Pauline McLoone; Afolabi Oluwadun; Mary Warnock; Lorna Fyfe (University Library System, University of Pittsburgh, 2016)
Problems with conventional treatments for a range of dermatological disorders have led scientists to search for new compounds of therapeutic value. Efforts have included the evaluation of natural products such as honey. Manuka honey, for example, has been scientifically recognised for its anti-microbial and wound healing properties and is now used clinically as a topical treatment for wound infections. In this review, scientific evidence for the effectiveness of honey in the treatment of wounds and other skin conditions is evaluated. A plethora of in vitro studies have revealed that honeys from all over the world have potent anti-microbial activity against skin relevant microbes. Moreover, a number of in vitro studies suggest that honey is able to modulate the skin immune system. Clinical research has shown honey to be efficacious in promoting the healing of partial thickness burn wounds while its effectiveness in the treatment of non-burn acute wounds and chronic wounds is conflicted. Published research investigating the efficacy of honey in the treatment of other types of skin disorders is limited. Nevertheless, positive effects have been reported, for example, kanuka honey from New Zealand was shown to have therapeutic value in the treatment of rosacea. Anti-carcinogenic effects of honey have also been observed in vitro and in a murine model of melanoma.  It can be concluded that honey is a biologically active and clinically interesting substance but more research is necessary for a comprehensive understanding of its medicinal value in dermatology.